Multimedia teen pregnancy [computer file] - Cambridge Research Group, Ltd.; Cambridge Educational (Firm) (South Charlston, WV : Cambridge Educational, 1998)
Shows the perils of teen sex , including pregnancy . Also covers parenting young children
Title from container
Booklet contains installation instruction
Windows system requirement ; 486DX with 66 Mhz ; 8 MB : 5 MB space available ; 4x300 kps CD-ROM ; 16 Bit audio card ; Operating system Window's @95 or newer version of the windows operating system
Macintosh system requirement ; 68030 or higher processor ; 4 MB RAM ; 8 MB space available ; Double speed - 300 KB/sec system 7.1 or higher
Keywords: Teenage pregnancy; Teenage mothers; Interactive multimedia